Synthesis, structural characterization, and in vitro anti-cancer activities of new phenylacrylonitrile derivatives - Özen, Furkan; Tekin, Suat; Koran, Kenan; Sandal, Süleyman; Görgülü, Ahmet Orhan (My University, 2016)
The present study was designed to both synthesize phenylacrylonitrile compounds (1a–k) and their anti-tumor activities on human breast cancer cell line (MCF-7) were determined. The structures of all the compounds were defined by melting point, elemental analysis, FT-IR, 1H, 13C, 13C-APT, and HETCOR-NMR spectroscopy. Anti-tumor activities of these compounds on cell viability were evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay against MCF-7. The MCF-7 cell lines were treated with 1, 5, 25, 50, and 100 ?M concentrations of phenylacrylonitrile compounds for 24 h. At the end of the experiments, 1a, 1b, 1c, 1g, and 1h compounds reduced cell viability (p < 0.01). Additionally, the anti-cancer activities of these compounds on MCF-7 were investigated by comparing IC50 values. In conclusion, while some of the synthesized phenylacrylonitrile compounds (1a, 1b, 1c, 1g, and 1h) have anti-tumor activity, other phenylacrylonitrile compounds (1d, 1e, 1f, 1k, and 1h) have no effect on human breast cell lines.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Anti-tumor activity; Breast cancer; MCF-7 NMR-spectroscopy; Phenylacrylonitrile